Study guides

☆☆

Q: 3a plus 2 plus 3a-5

Write your answer...

Submit

Still have questions?

Related questions

7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a

It is 6a + 4

-2(3a+2)+2=

a + 3a - 2 + 3a. Add the a + 3a + 3a = 7a. You can't combine the -2 & 7a so the solution is: 7a - 2.

5a

It can be simplified to: 3a^2 +10a+7 or factored as (3a+7)(a+1)

-2

9a^2 + 42at + 49t^2 = (3a + 7t)(3a + 7t)

2 + 3A + 9A = 2 + 12AThe numerical value depends on the value of 'A'.It changes whenever 'A' changes.

It is: 12a+2 when simplified

a2+3a-10 = (a-2)(a+5) when factored

x^3 + ax + 3a + 3x^2 = (x^3 + 3x^2) + (ax + 3a) = x^2(x + 3) + a(x + 3) = (x + 3)(x^2 + a)

(a + 2)(3a - 2)

Are you sure it's minus 49?If so, then:9a2 +42a -49={(3a)2 + 2·3a·7 + 72} -2·72=(3a -7)2 - (7·sqrt(2))2 (2nd binomial formula)={(3a -7) + (7·sqrt(2))} · {(3a -7) - (7·sqrt(2))} (3rd binomial formula)=(3a +2,89949) · (3a -16,89949).Otherwise if it's plus 49 then simpler:9a2 +42a +49={(3a)2 + 2·3a·7 + 72}=(3a -7)2.

6-3a**2+7+4a-5a+18 3a**2-1a+31

(3a - 4)(3a - 4)

3a^2 + 3a^2 = 6a^2 3a^2 - 3a^2 = 0 3a^2 x 3a^2 = 9a^4 3a^2 divided by 3a^2 = 1

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1

A = 3B = 5 ___________ 2 ( 3A + B) = 2 (9 + 5) = 2 (14) = 28

12

4a+3a-4 = 10 4a+3a = 10+4 7a = 14 a = 2

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)

= a + b - 2

Numerically, if the question looks like this:--(3a + 7b) - 8a - 4b + 2Then the answer is this:--3a - 7b - 8a - 4b + 2= -11a -11b + 2

Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).